Facilitators and Barriers to Glaucoma Screening Identified by Key Stakeholders in Underserved Communities: A Community-engaged Research Approach. Issue 5 (2nd May 2021) - Ballouz, Dena; Cho, Juno; Woodward, Maria A.; Elam, Angela R.; Musch, David C.; Zhang, Jason; Moroi, Sayoko E.; Johnson, Leroy; Cederna, Jean; Newman-Casey, Paula A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Précis: Community-engaged research (CER) enables researchers to identify community-specific barriers and facilitators to program implementation. Broadly applicable barriers to glaucoma care, such as Cost, Transportation, and Trust, and community-specific barriers, such as Language and Convenience/Access, were identified. Purpose: The aim was to identify the facilitators and barriers to implementing glaucoma screening programs in 2 community clinics. Methods: A concurrent mixed-methods process analysis using CER. Key stakeholders—including patients, providers, and staff members—from 2 community clinics were interviewed using a semistructured interview guide. Interviews had 2 parts: (1) asking patients about community-based facilitators and barriers to implementing glaucoma screening and care and (2) eliciting feedback about a personalized coaching program. The transcripts were coded using Grounded Theory. Number of participants and number of representative citations were counted per theme. The qualitative analysis was coded using Dedoose 8.3.17 (Los Angeles, CA). Results: Thematic saturation was reached after coding 12 interviews. 30 participants were interviewed, 13 from Hamilton Clinic (Flint, MI; 8 patients, 5 providers and staff members) and 17 from Hope Clinic (Ypsilanti, MI; 6 patients, 11 providers and staff members). The most commonly cited themes were: Priorities (98 citations, 30 participants), Knowledge (73, 26) Transportation (63, 26), Cost (60, 23), and Convenience/Access (63, 22). Broadly applicable barriers to glaucoma care, such as Cost, Transportation, and Trust were identified alongside community-specific barriers such as Language and Convenience/Access. Participants rated their likelihood to follow up with an ophthalmologist after participating in the personalized coaching program at a mean of 8.83 (on a scale of 1 to 10 with 10 being the most confident). Conclusions: CER enables researchers to identify community-specific barriers and facilitators, allowing more effective program implementation.